Toosendanin inhibits colorectal cancer cell growth through the Hedgehog pathway by targeting Shh. Issue 5 (2nd June 2022) - Zhang, Meng; Tao, Zhongyi; Gao, Lijuan; Chen, Fengyang; Ye, Yiping; Xu, Shifang; Huang, Wenkang; Li, Xiaoyu
Abstract: Colorectal cancer (CRC) is one of the most common gastrointestinal cancers worldwide. This complex and often fatal disease has a high mortality rate. The Hedgehog (Hh) signaling pathway is crucial in CRC. Many studies have indicated that Shh is overexpressed in cancer stem cells (CSCs), and shh overexpression is positively correlated with CRC tumorigenesis. New drugs that kill CRC cells through the Hh pathway are needed. Toosendanin (TSN), a natural triterpenoid saponin extracted from the bark or fruit of Melia toosendan Sieb. et Zucc, can inhibit various tumors. Here, we investigated the effects of TSN in CRC and explored the possible targets and mechanisms. Shh‐Light Ⅱ cells were treated with TSN and tested by dual luciferase reporter assays to determine the relationship with the Hh pathway. Cell Counting Kit‐8 (CCK‐8) assays were used to test the inhibitory effects of TSN on CRC cells. The expression of Hh components after TSN treatment was detected using western blots and quantitative reverse transcription polymerase chain reaction. Cellular thermal shift assays confirmed the targets of TSN. The same effects of TSN on xenograft tumor growth were investigated in vivo. The average weight, volume of the finally resected tumor, and the expression of Shh in the TSN‐treated groups were significantly lower than those of the control group. This result strongly suggested that TSN administration inhibited CRC growth in vivo. Our research preliminarily demonstrated that the target of TSN was Shh and that TSN inhibits CRC cell growth by inhibiting the Hh pathway, identifying a new anticancer molecular mechanism of TSN in CRC.